The importance of including neurosyphilis in the differenti al diagnosis of pati ents wit h cognitive decline and behavior disturbances - Santos, Hilda Maria Pascal Alves dos; Tostes, Camilee Pereira; Peixoto, Amanda B.; Figueira, Camile P.; Bortolini, Renata J.; Torrado, Carolina M.; Nery, José Augusto C. (Brazilian Journal of Sexually Transmitted Diseases, 2010)
Neurosyphilis results from infection of the brain, meninges or spinal cord by Treponema pallidum and develops in about 25-40% of persons who are not treated for syphilis. Dementia by neurosyphilis is a late manifestation of syphilis and was a frequent cause of dementia before the advent and widespread use of penicillin in the treatment of early stages of the disease. Although uncommon today, dementia of neurosyphilis still a differential diagnosis to consider in the face of atypical dementia or with manifestations front, particularly in socially disadvantaged populations socially. This case underscores the importance of early diagnosis of neurosyphilis, which clinicians should alert the possibility of neurosyphilis in patients who present with dementia, mainly belonging to the group of potentially reversible dementias, because proper treatment can reverse cognitive decline. And also, by increasing the number of syphilis cases in the last decade, particularly in combination with HIV, which can acelerate the course and alter the response to treatment of syphilis. This increased incidence of syphilis, also observed in Europe and the United States, could result in an increase in the number of cases of neurosyphilis observed in clinical practice.